72 Out-of-hospital cardiac arrest survivors undergoing emergency PCI have an excellent neurological recovery. (May 2019) - ramachenderam, liandra rams; Mechery, Anthony; Isherwood, Peter; Abeysinghe, Neil; Zaphiriou, Alexander; George, Sudhakar; Nadir, M. Adnan; Ludman, Peter; Doshi, Sagar; Townend, Jonathan; khan, sohail
Abstract : Introduction: Out-of-hospital cardiac arrest (OHCA) is associated with a low survival to discharge rate. We aimed to evaluate the outcome of early Percutaneous Coronary Intervention (PCI) on the mortality rates of patients with OHCA and their neurological recovery post-intervention. Methods: Outcomes of all patients presenting to our centre with OHCA who received PCI over a 3-year period were analysed (January 2015 - December 2017). Univariate analysis was performed. Results: 65 patients were identified (80% Males, Mean age 59.9 ± 14.2 years). Chest compressions were undertaken in 60.0% of patients. The most common rhythm identified was Ventricular Fibrillation (86.2%), followed by PEA (9.2%), Ventricular Tachycardia (4.6%) and Asystole (4.6%). The mean time for patients to arrive at the cardiac centre was 51.4± 20.7 minutes. Post-arrest ECG revealed ST-elevation (STEMI) in 53 (81.5%) patients. 42 (64.4%) received ventilation pre-angiography and 45 (69.2%) were transferred to Intensive Care Unit (ITU) post-angiography. 18 (27.7%) were in cardiogenic shock. There was no statistical significance in the mortality rates between patients with STEMI and non-STEMI (53 vs 12; p=0.43), see Table 1. 54 patients (83.1%) survived to discharge, 30-day survival 53(81.6%), 6-month survival 53(81.6%). 31 ventilated patients (73.8%) survived to discharge, 30-days and 6-months whereas all (100%) non-ventilated patients (n=23) survived to discharge and 30-days and 22 survived (95.7%) at 6-months (73.8 vs 100%; p=0.04). 12 patients in shock (66.7%) survived to discharge, 30-days and 6-months whereas 42 non-shocked patients (89.4%) survived to discharge, 30-days and 6-months (66.7 vs 89.4%, p=0.06). Cerebral Performance Category (CPC) score at 30-days was as follows; 48 (73.8%) scored 1, 3 (4.6%) scored 2, 2 (3.1%) scored 3, 1 (1.5%) scored 4 and 11 (16.9%) scored 5. Significantly more patients were in CPC 1 to 3 than 4–5 (53 vs 12; p<0.001), see Table 2. Conclusion: In our cohort of patients presenting with OHCA who underwent PCI, we observed an excellent survival to discharge rate. Poor neurological recovery is seen in only a minority of patients who have received PCI after successful OHCA. Conflict of Interest: None